Teaching tactical creativity in sport. Research and practice - Memmert, D. (Routledge studies in physical education and youth sport, 2015)
Creativity is an essential component of sport performance. The player who can make decisions that are both unexpected - and therefore less easily predicted by his/her opponent - and appropriate is the player who is likely to be successful. In this ground-breaking new book Daniel Memmert explores the concept of tactical creativity, introducing a new theoretical framework based on extensive empirical research. He argues for the importance of encouraging divergent thinking abilities at an early age, and explains how tactical creativity sits alongside conventional approaches to 'teaching games for understanding'. The book outlines essential rules for environmental and training conditions, and suggests a wide range of game forms for teaching and coaching tactical creativity to children and young people. This is important to all students, researchers, coaches and teachers working in physical education, sports coaching, sport psychology or skill acquisition.